2001
DOI: 10.1111/j.1471-0528.2001.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal endothelial soluble cell adhesion molecules with isolated small for gestational age fetuses: comparison with pre‐eclampsia

Abstract: Objective 1.To evaluate the activation profile of the endothelium in pregnancies complicated by small for gestational age fetuses compared with pre-eclampsia and normal pregnancy, by measuring the plasma levels of soluble adhesion molecules soluble E-selectin, intercellular cell adhesion molecule-1 and vascular cell adhesion molecule-1. 2. To determine whether soluble adhesion molecules were related to the severity of small for gestational age fetuses and pre-eclampsia. Design Observational study. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…However, there were no statistical differences in the levels of E-selectin between mild and severe PE (14). In France, Bretelle et al and Bersinger et al in Switzerland reported similar results in increasing Eselectin in PE (15,16). In Carty DM et al study, E-selectin concentrations were higher in women who develop PE in preterm labor lower than 28 weeks (8).…”
Section: Resultssupporting
confidence: 56%
“…However, there were no statistical differences in the levels of E-selectin between mild and severe PE (14). In France, Bretelle et al and Bersinger et al in Switzerland reported similar results in increasing Eselectin in PE (15,16). In Carty DM et al study, E-selectin concentrations were higher in women who develop PE in preterm labor lower than 28 weeks (8).…”
Section: Resultssupporting
confidence: 56%
“…Those microparticles would induce endothelial dysfunction [32] and neutrophil activation with release of neutrophil extracellular traps full of DNA [29] . Endothelial cell activation has been documented in IUGR pregnancies [33] with modification of specific endothelial marker concentrations [34] . There is also an increased risk of developing hypertension or ischemic cardiopathy for women who carried a growth-restricted fetus [35] , suggesting maternal endothelial damage in isolated IUGR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, activation of the innate immune system and an exaggerated maternal systemic inflammatory response has been described in preeclampsia[67, 71, 73, 75, 100106] and, to a lesser extent, in SGA. [72,75,104,106108] Evidence to support this view includes: 1) leukocyte activation, [72,73] 2) increased maternal serum concentration of pro-inflammatory cytokines such as TNF (tumor necrosis factor)-alpha, [108] and 3) increased plasma markers of endothelial cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…[72,75,104,106108] Evidence to support this view includes: 1) leukocyte activation, [72,73] 2) increased maternal serum concentration of pro-inflammatory cytokines such as TNF (tumor necrosis factor)-alpha, [108] and 3) increased plasma markers of endothelial cell activation. [75,76]…”
Section: Introductionmentioning
confidence: 99%